Ruins of Identity Ethnogenesis in the Japanese Islands - Hudson, Mark James (University of Hawaii Press, 1999)
Many Japanese people consider themselves to be part of an essentially unchanging and isolated ethnic unit in which the biological, linguistic, and cultural aspects of Japanese identity overlap almost completely with each other. In its examination of the processes of ethnogenesis (the formation of ethnic groups) in the Japanese Islands, Ruins of Identity offers an approach to ethnicity that differs fundamentally from that found in most Japanese scholarship and popular discourse. Following an extensive discussion of previous theories on the formation of Japanese language, race, and culture and the nationalistic ideologies that have affected research in these topics, Mark Hudson presents a model of a core Japanese population based on the dual origin hypothesis currently favored by physical anthropologists.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2021)
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social